Risk of Second Malignant Neoplasm in Familial Non-Medullary Thyroid Cancer Patients - Capezzone, Marco; Sagnella, Alfonso; Cantara, Silvia; Fralassi, Noemi; Maino, Fabio; Forleo, Raffaella; Brilli, Lucia; Pilli, Tania; Cartocci, Alessandra; Castagna, Maria Grazia (Frontiers in Endocrinology, 2022)
Introduction. Survival rates in patients with non-medullary thyroid carcinoma (NMTC) are high increasing the possibility to develop a second malignant neoplasm (SMN). Many studies investigated the relationship between increased risk of SMN in NMTC patients treated with radioiodine but few data are available about the impact of family history (FH) of thyroid cancer on SMN risk. Purpose. To assess the risk of SMN in a large cohort of sporadic and familial NMTC using the standardize incidence ratio (SIR). Patients and methods. We studied 918 NMTC patients (73.9% females) followed for a median follow-up of 9 years. In 798/918 (86.9%) patients NMTC was sporadic while the remaining 120 (13.1%) were familial NMTC (FNMTC). Results. We identified 119/918 (13%) patients with SMN in association with NMTC. NMTCs had an increased risk of SMN when compared to the general population (SIR 2.1, 95% CI 1.7-2.5). The rate of SMN for all sites was significantly higher in familial compared to sporadic NMTC (20% versus 11.9%, p=0.01), primarily driven by families with more than two affected members. The risk of SMN was remarkably higher for breast cancer, especially in familial cases (SIR 22.03, 95% CI 14.4-41.2) compared to sporadic cases (SIR:17, 95% CI 11.9-24.6). Conclusions. NMTC patients have a higher risk of SMN compared to the general population and this risk is much higher in patients with FNMTC. This observation raises the hypothesis that genetic risk factors for a first cancer may predispose to SMN, especially among individuals with familial clustering of the same or other tumors.